The impact of emotional stimuli on response inhibition in an inpatient and day-hospital patient psychosomatic cohort - Westbomke, Sina; Schag, Kathrin; Derntl, Birgit; Zipfel, Stephan; Stengel, Andreas (Frontiers in Psychiatry, 2023)
ABSTRACT Objectives To correctly recognize and respond to your counterparts`s emotion is essential for a successful get-together. To ensure this, emotional processes and inhibitory control are linked and interact with each other. However, this interaction can be altered in several men-tal disorders. In a group of psychosomatic patients, we investigated possible differences in the response inhibition between neutral and emotional stimuli and whether a psychosomatic inpatient and day-hospital patient treatment influences response inhibition profiles. Methods 101 patients, diagnosed with different psychiatric diagnoses (77 females, 41.43±13.13 years) completed an emotional stop-signal task (ESST) and an impulsive be-havioral scale upon admission in an inpatient and day-hospital patient treatment on a psy-chosomatic ward (T0) and at discharge (T1). Patients with depressive disorders completed the test again after one year (Follow-up measurement T2, n=22). Emotional stimuli were angry and neutral faces. Stop-signal reaction time (SSRT) and stop-signal delay (SSD) were calculated as main behavioral parameters. Results We found a significantly higher SSRT for neutral than angry faces both at admis-sion (8.538 ms, p<.001) and discharge (11.142 ms, p<.001), with a matching higher SSD for angry than neutral faces at both timepoints (T0: 8.360 ms, p<.001, T1: (6.950 ms, p<.001). The SSRT for angry faces significantly decreased after treatment (-8.485 ms, p=.0110). For neutral faces the decrease failed to reach significance (-5.881 ms, p=.250). A significant decrease of SSRT for neutral faces in patients with depressive disorders was found one year after discharge compared to admission (-19.040 ms, p=.0380). Conclusion Our data demonstrates a decreased response inhibition for neutral compared to emotional stimuli and an improved response inhibition for angry faces after discharge in a psychosomatic inpatient and day-hospital patient cohort. Additionally, patients with depres-sive disorders displayed a significantly better response inhibition for neutral faces one year after discharge compared to the baseline measurement. With this study we provide more evidence for altered emotional response inhibition in different mental disorders and a hint that psychosomatic inpatient and day-hospital patient treatment may help to normalize it, even if the effects remained small and it needs further research to prove causality.